2004
DOI: 10.1590/s0037-86822004000100012
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pulmonary tuberculosis in HIV seropositive and seronegative patients in a Northeastern region of Brazil

Abstract: The aim of this study was to analyse the clinical, epidemiological and bacteriological features present in 60 pulmonary tuberculosis patients who were also infected with human immunodeficiency virus (HIV) and to compare these with 120 TB patients who were not infected with HIV. The patients with pulmonary tuberculosis and HIV coinfection were mostly male (p = 0.001), showed a higher frequency of weight loss >10 kilos (p <0.001), had a higher rate of non-reaction result to the tuberculin skin test (p <0.001), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
1
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 9 publications
5
27
1
6
Order By: Relevance
“…The extrapulmonary clinical form of TB was more common in HIVpositive patients than in HIV-negative patients (25.5% vs. 14%). (11)(12)(13) In terms of treatment outcome, we used only the following outcome measures: cure, abandonment, death or relocation. Of the TB/HIV co-infected patients, 52.5% were cured, 11% abandoned treatment, 33% died, and 3.5% were relocated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extrapulmonary clinical form of TB was more common in HIVpositive patients than in HIV-negative patients (25.5% vs. 14%). (11)(12)(13) In terms of treatment outcome, we used only the following outcome measures: cure, abandonment, death or relocation. Of the TB/HIV co-infected patients, 52.5% were cured, 11% abandoned treatment, 33% died, and 3.5% were relocated.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors (11) have reported that TB/HIV coinfection is more common in males, a condition not observed among individuals infected with TB alone. In the present study, a similar situation was observed: males were more often affected by such co-infection than were females.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies were laboratory-based. Data were collected retrospectively in all the studies but two (Liberato et al 2004, Brito et al 2010. Seven studies were designed to enrol both HIV-positive and HIVnegative patients.…”
mentioning
confidence: 99%
“…Data concerning resistance to specific anti-TB drugs among HIV-infected patients were discernible in seven of the selected studies (Santi et al 2001, Lemos et al 2004, Liberato et al 2004, Rozman et al 2007, Wolfart et al 2008, Zamarioli et al 2009, Nunes et al 2010. The global resistance rate (both primary and acquired) to isoniazid alone ranged from 3.6-18.7%, while resistance to rifampicin alone ranged from 0.2-9.1%.…”
mentioning
confidence: 99%
“…Froes e cols 14 em Minas Gerais obtiveram um acréscimo de 19,4% no diagnóstico da TB com a realização da cultura; Boffo e cols 6 alcançaram um rendimento maior da cultura em 10,2% no diagnóstico de sintomáticos respiratórios; e Liberato e cols 23 , no nordeste brasileiro, verificaram acréscimo de 10,6% na positividade da cultura em relação à baciloscopia do escarro de pacientes HIV-positivos.…”
Section: Discussionunclassified